Demographic and Psychosocial Predictors of Housing Security in Older Lesbian and Gay Australians. (July 2019) - Alba, Beatrice; Lyons, Anthony; Waling, Andrea; Minichiello, Victor; Hughes, Mark; Barrett, Catherine; Fredriksen Goldsen, Karen; Blanchard, Michelle; Irlam, Corey
This study examined housing security among 679 lesbian women and gay men aged 60 years and older living in Australia. We examined a range of potential demographic and psychosocial predictors of whether participants felt that their housing situation was secure. Overall, most participants (89%) felt that their housing situation was secure. We found that the sense of housing security was greater among those who were younger, had people they felt they could depend on, had better self-rated health, and had fewer experiences of sexual orientation discrimination over the past year. In addition, housing security was greater among those who owned their own home and had no mortgage, compared with those who had a mortgage, were renting, or had some other living arrangement. No other demographic variables were significant predictors of housing security. These results can be useful in targeting groups that may be particularly vulnerable to a lack of housing security.